Role of biobanking in managing large-scale epidemiological studies - M. S. Pokrovskaya; A. L. Borisova; V. A. Metelskaya; I. A. Efimova; Yu. V. Doludin; V. A. Kozlova; Z. Z. Serebryanskaya; Yu. A. Balanova; A. N. Meshkov; A. V. Pustelenin; A. E. Imaeva; S. A. Shalnova; et al. (Кардиоваскулярная терапия и профилактика, 2021)
The success and quality of large-scale epidemiological studies depends entirely on biomaterial quality. Therefore, when arranging the third Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF-3) study, increased attention was paid to specifics of collection, processing and further transportation of biological samples and related clinical and anthropometric data of participants from regional collection centers to Biobank.Aim. To develop a methodology for collection of high-quality biomaterials within the large-scale epidemiological study, involving the sampling, processing, freezing of blood and its derivatives (serum, plasma) in the regions, followed by transportation and storage of obtained biomaterial in the Biobank of National Medical Research Center for Therapy and Preventive Medicine (Moscow).Material and methods. To conduct the ESSE-RF-3 study, a design was developed, according to which the collection of venous blood samples in a total volume of 29,5 ml from each participant is planned in all participating regions in order to obtain and store samples of whole blood, serum and two types of plasma.Results. On the basis of international biobanking standards, ethical norms, experience from ESSE-RF and ESSE-RF-2, and literature data, a protocol for biobanking of blood and its derivatives was developed. The type and number of serum and plasma aliquots obtained, the required standard technical means and consumables, as well as logistic biomaterial requirements were determined. Training programs for regional participants were developed. By the beginning of August 2021, 180 thousand samples of whole blood, serum and plasma from more than 23 thousand participants from 28 Russian regions were collected, processed and stored.Conclusion. The presented work made it possible to assess and confirm the compliance of developed biobanking protocol with quality requirements. However, due to the coronavirus disease 2019 pandemic, by August 2021, the Biobank did not reach the maximum effectiveness predicted for the ESSE-RF-3 project.